1986
DOI: 10.1002/jso.2930330306
|View full text |Cite
|
Sign up to set email alerts
|

Fatal metastatic cystosarcoma phyllodes in an adolescent female: Case report and review of treatment approaches

Abstract: The third reported case of fatal malignant cystosarcoma phyllodes in an adolescent female is described. The patterns of local recurrence and distant spread in this case, including the response to treatment, were similar to those reported in the first reported case in this age group. A review of the treatment recommendations for cystosarcoma phyllodes revealed that the surgical procedure of choice for the malignant variant has remained controversial, and the conclusions regarding the ineffectiveness of radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Local failure rates for benign tumors range between 5-15% 1,4,9,15 and 20 -30% for malignant tumors. 9,10,15,27,28,29 In the current series, the 10-year actuarial local failure rate was 8%. Local failure occurred in 3 of 71 patients (4%) with benign or indeterminate tumors.…”
Section: Discussionmentioning
confidence: 97%
“…Local failure rates for benign tumors range between 5-15% 1,4,9,15 and 20 -30% for malignant tumors. 9,10,15,27,28,29 In the current series, the 10-year actuarial local failure rate was 8%. Local failure occurred in 3 of 71 patients (4%) with benign or indeterminate tumors.…”
Section: Discussionmentioning
confidence: 97%
“…',3,'6, 27 We, however, observed excellent tumor responses to radiation therapy in all three of our patients. Others also reported control of metastatic disease with radiation…”
Section: Discussionmentioning
confidence: 81%
“…Local failure rates for benign tumors range between 5-15% and 20-30% for malignant tumors. 15,19,22,23,26,[31][32][33] Margins of 1-2 cm have been recommended, and enucleation alone is insufficient. 19,21,22,25,26 de-Roos et al found positive margins in all patients who sustained a local recurrence after local excision.…”
Section: Discussionmentioning
confidence: 99%
“…24 The reported rates of distant metastasis for patients with malignant tumors range from 25-40%. 9,19,25,31 The role of adjuvant radiotherapy is not well established. August et al suggested radiotherapy after wide local excision for high risk lesions (tumour >5 cms, presence of stromal overgrowth, >10 mitoses/10hpf, infiltrative margins), for local recurrence would likely be avoided in 90% or more of these patients.…”
Section: Discussionmentioning
confidence: 99%